اختبار أثر الرافعة وسلوك التذبذب في سوق دمشق للأوراق المالية - محمد, سام; الحسين, محمد; غانم, عدنان (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف هذا البحث إلى اختبار مدى تمتع سوق دمشق للأوراق المالية ببعض الخصائص والسمات العامة التي تتصف بها معظم الأسواق المالية العالمية والعربية، وهي: خاصية عنقودية التباين، وخاصية التحول إلى المتوسط، و أثر الرافعة، وذلك بتطبيق نموذجي GARCH و EGARC، باستخدام سلسلة زمنية تتضمن عوائد مؤشر السوق منذ انطلاق المؤشر في 31/12/2009 لغاية 16/4/2013. بحسب النتائج، تتمتع عوائد مؤشر سوق دمشق بخاصية عنقودية التباين، أي أن القيم الكبيرة للتذبذب اليوم ستكون متبوعة بقيم كبيرة للتذبذب في الغد. كما يتمتع المؤشر بخاصية أثر الرافعة، أي أن الصدمات السالبة سيكون لها أثر على مستوى التباين المشروط أكثر مما لو كانت الصدمة موجبة. لكن لا يتمتع المؤشر بخاصية التحول إلى المتوسط بسبب اتصاف التذبذب بالانفجاري. This paper aims to check whether the index (DWX) of Damascus Stock Exchange (DSE) is characterized by some of the stylized facts of most of the international and Arab stock markets, as: Volatility Clustering, Reversion to the Mean, and the Leverage Effect. The GARCH and EGARCH models were applied using the returns series of DWX for a period from 31/12/2009 till 16/4/2013. The findings showed that DSE is characterized by: 1) Volatility Clustering, meaning that large volatility today will be followed by large volatility tomorrow, 2) Leverage Effect, meaning that volatility tends to rise more after a negative shock that a positive one, 3) But the DWX is not characterized by the reversion to the mean process, due the explosive volatility of the index.